Optimal Energy Management for off-Grid Hybrid Renewable Energy Systems - Suwi, Owdean M.; Justo, Jackson J. (Tanzania Journal of Engineering and Technology, 2025)
A photovoltaic (PV)/wind/battery/Generator-Set hybrid power system's energy dispatch is discussed in this research, along with the ideal solution. The optimization model enables the hybrid power system's generating devices to share power appropriately. The main goals are to minimize fuel consumption and costs and maximize the usage of Renewable Energy Sources (RES). The proposed simulation plan succeeds in lowering fuel costs because the diesel generator only kicks on at night and in the early morning when the energy from RES is insufficient to supply the load. The load is supplied with power, and the battery is charged throughout the day, when the production of electricity from the wind and solar generators is highest. The use of diesel is minimal. However, based on their particular characteristics and the operational limitations of the system, the generating devices effectively share the power needed from the hybrid power system.